2021
DOI: 10.3171/2019.10.jns191991
|View full text |Cite
|
Sign up to set email alerts
|

Predictor of 90-day functional outcome after mechanical thrombectomy for large vessel occlusion stroke: NIHSS score of 10 or less at 24 hours

Abstract: OBJECTIVEMechanical thrombectomy is the established treatment for acute ischemic stroke due to large vessel occlusion (LVO). The authors sought to identify early predictors of a favorable outcome in stroke patients treated with mechanical thrombectomy.METHODSConsecutive patients with ischemic stroke due to LVO who underwent mechanical thrombectomy at a Comprehensive Stroke Center in the US between 2016 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 12 publications
2
36
0
Order By: Relevance
“…To date, several independent factors have been identified by some authors which reportedly worsen the functional status of patients undergoing MT for stroke. These include older age, low ASPECTS scores, and high NIHSS scores [12][13][14]17,18]. In terms of the importance of age and neurological status, we have confirmed the reports of other authors; we have also gained more experience concerning the influence of a patient's clinical profile on the outcome of endovascular therapy and their post-stroke functional status in the acute period of stroke.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…To date, several independent factors have been identified by some authors which reportedly worsen the functional status of patients undergoing MT for stroke. These include older age, low ASPECTS scores, and high NIHSS scores [12][13][14]17,18]. In terms of the importance of age and neurological status, we have confirmed the reports of other authors; we have also gained more experience concerning the influence of a patient's clinical profile on the outcome of endovascular therapy and their post-stroke functional status in the acute period of stroke.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, attempts are being made to identify the parameters to determine the outcome of endovascular therapy in acute stroke patients. The most common findings are age, the patients' neurological status during the ultra-acute stage of stroke, and the ASPECTS score [12][13][14]. Atrial fibrillation, diabetes, previous exposure to anticoagulation, the morphotic parameters of blood, and inflammatory parameters all have a conflicting status in several studies [12,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The most susceptible regions of the brain to cerebral ischemia are the hippocampus and cortex, and data mining for circRNAs in the cortex is therefore valuable in establishing the mechanisms underlying damage and self-repair poststroke. A large number of studies have shown that the 24-hour time point is the most severe time point for nerve damage after cerebral ischemia and reperfusion injury [ 50 , 52 55 ]. We detected 24,858 circRNAs, among which 20,199 were novel and 4,659 were known.…”
Section: Discussionmentioning
confidence: 99%
“…The main outcome measures we sought at the vascular recanalization rate, the rate of incidence of adverse events, the rate of mortality within 90 days, preoperative and postoperative 7 days NIH Stroke Scale score, [ 19 , 20 ] postoperative 90 days Modified Rankin Scale score. [ 21 ]…”
Section: Methods and Analysismentioning
confidence: 99%